Partial and total relative correctness for analysis of real-time systems - Szmuc, Tomasz Bartłomiej (1948- ) (Zielona Góra: Uniwersytet Zielonogórski)
This paper is a continuation of the former works dealing with the correctness verification of concurrent systems. The correctness in the sense of criterion (relative correctness) is a basic notion in these investigations. Two classes of the problem: partial and total relative correctness are considered. Formal tools and conception of computer support for the correctness verification are developed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka